Antisenescence effect of mouse embryonic stem cell conditioned medium through a PDGF/FGF pathway. Issue 3 (16th December 2015) - Bae, Yun‐Ui; Choi, Joon‐Hyuk; Nagy, Andras; Sung, Hoon‐Ki; Kim, Jae‐Ryong
Abstract : Cellular senescence, an irreversible state of growth arrest, underlies organismal aging and age‐related diseases. Recent evidence suggests that aging intervention based on inhibition of cellular senescence might be a promising strategy for treatment of aging and age‐related diseases. Embryonic stem cells (ESCs) and ESC conditioned medium (CM) have been suggested as a desirable source for regenerative medicine. However, effects of ESC‐CM on cellular senescence remain to be determined. We found that treatment of senescent human dermal fibroblasts with CM from mouse ESCs (mESCs) decreases senescence phenotypes. We found that platelet‐derived growth factor BB in mESC‐CM plays a critical role in antisenescence effect of mESC‐CM through upregulation of fibroblast growth factor 2. We confirmed that mESC‐CM treatment accelerates the wound‐healing process by down‐regulating senescence‐associated p53 expression in in vivo models. Taken together, our results suggest that mESC‐CM has the ability to suppress cellular senescence and maintain proliferative capacity. Therefore, this strategy might emerge as a novel therapeutic strategy for aging and age‐related diseases.—Bae, Y.‐U., Choi, J.‐H., Nagy, A., Sung, H.‐K., Kim, J.‐R. Antisenescence effect of mouse embryonic stem cell conditioned medium through a PDGF/FGF pathway. FASEB J. 30, 1276–1286 (2016). www.fasebj.org